ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MENYIMPANG PADA REMAJA - Mentari, Gilang Sri; Jumaini, Jumaini; Arneliwati, Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adolescence is a very critical period in human development stage, where multi dimension change happens such as biologic, cognitive, psychological and social change. Many changes in this period make adolescent find more problems that could be a kind of deviant behavior. This study aimed to analyze the factors associated with deviant behavior in adolescent. The design of this research was descriptive correlation using cross sectional approach. The sample of this research was 201 students of SMP N 15 Pekanbaru using stratified random sampling technique. The instrument used was a questionnaire that has been tested for validity and reliability. The univariate analysis was used to know the frequency of distribution. Bivariate analysis used was chi-square test. The result showed that there were significant relationship between explanation of internet with light deviant behavior (p value = 0,020) and heavy deviant behavior (p value = 0,031). The result showed there were no significant relationship between self control and parent communication pattern with light, medium, and heavy deviant behavior, and internet explanation with medium deviant behavior. School has to warn and give educated punishment to student and also strengthen Counseling teacher participation, so it will decrease the risk of deviant behavior in adolescent.Keywords: Adolescent, deviant behavior, explanation of internet, parent communication pattern, self control